2021
DOI: 10.31260/repertmedcir.01217372.1008
|View full text |Cite
|
Sign up to set email alerts
|

Frecuencias genotípicas y alélicas de apolipoproteina e (APOE) en una muestra de adultos en Bogotá

Abstract: Introducción: la apolipoproteína E (APOE) es una glicoproteína implicada en el transporte de moléculas lipídicas. Se han descrito tres alelos del gen APOE: Ɛ2, Ɛ3 y Ɛ4. Varios estudios demuestran asociación de la isoforma APOE4 con Alzheimer de inicio tardío. Objetivos: determinar las frecuencias genotípicas y alélicas del gen APOE en una muestra de adultos en Bogotá. Materiales y métodos: estudio observacional descriptivo de corte transversal. A partir de una muestra de sangre periférica se extrajo ADN genómi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…27 , 28 The genotype frequencies of the APOΕ gene in our sample studied were similar to those described in Colombian, Latin American, and world literature. 26 A hazard ratio (HR) of 1.35 (95%CI 1.00–1.83) has been reported between the presence of the ϵ4 allele and the risk of AD, 29 whereas in a previous study in Colombia, it has been observed that the relationship has an OR of 5.1. 30…”
Section: Discussionmentioning
confidence: 96%
“…27 , 28 The genotype frequencies of the APOΕ gene in our sample studied were similar to those described in Colombian, Latin American, and world literature. 26 A hazard ratio (HR) of 1.35 (95%CI 1.00–1.83) has been reported between the presence of the ϵ4 allele and the risk of AD, 29 whereas in a previous study in Colombia, it has been observed that the relationship has an OR of 5.1. 30…”
Section: Discussionmentioning
confidence: 96%